Migrant integration policy in Sweden after 2015. A revised approach in the shadow of the migration crisis - Banaś, Monika (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
This article investigates a modified approach to the principles of migrant integration policy in Sweden – the highest ranked country included in the Migration Integration Policy Index (MIPEX 2015). The modified approach has two main causes: a weaker than initially assumed effectiveness of integration mechanisms applied until 2015 and the migration crisis of 2015 with its global and regional effects. The text critically analyses one of the most important areas of the integration policy – the labour market seen in a broader context including other dimensions of integration, like family reunification, political participation or access to nationality. Based on field research carried out in Sweden in 2018 and 2019, supplemented with a critical analysis of the literature on the subject, I conclude that integration concepts and solutions employed did not fully meet the stated goals. This deficit can be observed in the labour markets’ still present and in some cases increasing gaps between the autochthons and the migrants. Much more organizational and financial effort must be directed towards the areas of ​​education and schooling. In addition, in all of the domains, a more active participation of migrants is required.